FEATURES OF TAX SYSTEM REFORMING OF UKRAINE - Snachov, M. P.; Yanushevska, Yu. V. (Science and Transport Progress, 2008)
In this article some problems of the taxation system ofUkrainein modern conditions are investigated and, taking into account the experience of foreign countries, the recommendations related to the perfection of taxation mechanism for physical and juridical persons are offered.